Biosynthesis of silver nanoparticles by using ganoderma-mushroom extract - Ekar, S. U.; Khollam, Y. B.; Koinkar, Pankaj M.; Mirji, S. A.; Mane, R. S.; Naushad, M.; Jadhav, S. S. (Modern Physics Letters B, 2015)
Present study reports the biochemical synthesis of silver nanoparticles (Ag-NPs) from aqueous medium by using the extract of medicinal mushroom Ganoderma, as a reducing and stabilizing agents. The Ag-NPs are prepared at room temperature by the reduction of Ag+ to Ag in aqueous solution of AgNO3. The resultant particles are characterized by using UV-visible spectroscopy, Fourier transform infrared (FTIR) spectroscopy and transmission electron microscopy (TEM) measurement techniques. The formation of Ag-NPs is confirmed by recording the UV-visible absorption spectra for surface plasmon resonance (SPR) where peak around 427 nm. The prominent changes observed in FTIR spectra supported the reduction of Ag+ to Ag. The morphological features of Ag-NPs are evaluated from HRTEM. The spherical Ag-NPs are observed in transmission electron microscopy (TEM) studies. The particle size distribution is found to be nearly uniform with average particle size of 2 nm. The Ag-NPs aged for 15, 30, 60 and 120 days showed no profound effect on the position of SPR peak in UV-visible studies, indicating the protecting/capping ability of medicinal mushroom Ganoderma in the synthesis of AgNPs.
Keywords: Biosynthesis; Ganoderma; medicinal mushroom; silver nanoparticles; UV-visible spectroscopy